2018
DOI: 10.1002/ardp.201700386
|View full text |Cite
|
Sign up to set email alerts
|

Reagent‐induced asymmetric induction in addition reaction of reduced glutathione onto bis‐Mannich chalcones

Abstract: The stereochemistry of non-enzyme catalyzed nucleophilic addition of GSH to 4'-hydroxychalcone 1 and its bis-Mannich derivative 2 was investigated at different pH values (pH 3.2, 6.1, 7.4, and 8.0). The stereochemical outcome of the reactions was evaluated by HPLC-UV-Vis method. Under strongly acidic conditions (pH 3.2), an unexpected diastereoselective addition of GSH onto the bis-Mannich derivative 2 was observed. Such a selectivity could not be observed in the similar reaction of 2 with N-acetylcysteine. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…This reaction leads to the reduction of GSH levels, which are related to cytotoxic effects, such as the activation of apotoses or to make the cells susceptible to oxidative damage. 32,33,[39][40][41]…”
Section: Antitumor Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…This reaction leads to the reduction of GSH levels, which are related to cytotoxic effects, such as the activation of apotoses or to make the cells susceptible to oxidative damage. 32,33,[39][40][41]…”
Section: Antitumor Testsmentioning
confidence: 99%
“…In recent years, our research group has been dedicated to synthesis, characterization and antitumor evaluation of chalcone derivatives. [29][30][31][32][33][34] The bioactivity of these compounds is associated with cellular thiols as glutathione reduced (GSH). Therefore, our group reported the reaction of Mannich bases and hydroxychalcone with GSH and the stereochemistry of non-enzyme nucleophilic addition of GSH to hydroxychalcone and Mannich base derivative at different pH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural modification of chalcones could result in different GSH-reactivity (Amslinger 2010;Maydt et al 2013;Gomes et al 2017). Earlier, we have investigated GSHreactivity of analogous 4′-hydroxychalcones and their bis-Mannich derivatives (Bernardes et al 2017;Bernardes et al 2018). It was found that the Mannich derivatives showed a significantly different reactivity (Bernardes et al 2017) and stereoselectivity (Bernardes et al 2018) from those of the respective non-Mannich derivatives when the reactions were conducted under acid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, we have investigated GSHreactivity of analogous 4′-hydroxychalcones and their bis-Mannich derivatives (Bernardes et al 2017;Bernardes et al 2018). It was found that the Mannich derivatives showed a significantly different reactivity (Bernardes et al 2017) and stereoselectivity (Bernardes et al 2018) from those of the respective non-Mannich derivatives when the reactions were conducted under acid conditions. Furthermore; we have synthesized several 2′-benzensulfonamido-chalcones and their cyclic quinolone derivatives (de Castro et al 2016;de Castro et al 2017;d'Oliveira et al 2018).…”
Section: Introductionmentioning
confidence: 99%